In‐Plane Assembled Single‐Crystalline T‐Nb2O5 Nanorods Derived from Few‐Layered Nb2CTx MXene Nanosheets for Advanced Li‐Ion Capacitors. Issue 12 (8th October 2020) - Qin, Li; Liu, Yang; Xu, Senyang; Wang, Shichao; Sun, Xuan; Zhu, Shuhao; Hou, Linrui; Yuan, Changzhou
Abstract: Lithium‐ion capacitors (LICs) have attracted enormous interest thanks to their competitive power/energy densities and long‐duration lifespan. However, the sluggish insertion kinetics of battery‐type anodes seriously limits comprehensive performance of LICs. It is therefore imperative yet significant to develop advanced anodes with high‐rate Li + intercalation. Herein, first the in‐plane assembled single‐crystalline orthorhombic Nb2 O5 nanorods (T‐Nb2 O5 NRs) are designed and constructed via efficient hydrothermal and subsequent annealing treatment by employing few‐layered Nb2 CT x nanosheets as a niobium‐based precursor. The inherent formation mechanism of single‐crystalline T‐Nb2 O5 NRs is tentatively proposed. When evaluated as anode material for LICs, the T‐Nb2 O5 NRs are endowed with robust crystalline skeletons and high diffusion dynamics benefiting from their appealing structure merits, and they exhibit a high‐rate capacity of ≈ 147 mAh g −1 at 2.0 A g −1 . The lithium storage process of the resultant single‐crystalline T‐Nb2 O5 is unveiled as well with in situ X‐ray diffraction analysis. Furthermore, the T‐Nb2 O5 NR‐based LICs display a large energy density of ≈ 35.6 Wh kg −1 at 8 kW kg −1, along with exceptional capacity retention of ≈ 95% over 4000 cycles at 0.5 A g −1 . More significantly, the devised synthetic methodology and in‐depth insights here will stimulate extensive development of single‐crystalline T‐Nb2 O5 NRs for next‐generation LICs and beyond. Abstract : 1D in‐plane assembled single‐crystalline T‐Nb2 O5 nanorods derived from 2D few‐layered Nb2 CT x nanosheets are first designed, and they exhibit exceptional Li‐storage properties for Li‐ion capacitors as anodes, thanks to their unique structural merits.